Demystifying the Mystery Room. (20th February 2019) - Wenmackers, Sylvia
Abstract: The Mystery Room problem is a close variant of the Mystery Bag scenario (due to Titelbaum). It is argued here that dealing with this problem requires no revision of the Bayesian formalism, since there exists a solution to this problem in which indexicals or demonstratives play no essential role. The solution does require labels, which are internal to the probabilistic model. While there needs to be a connection between at least one label and one indexical or demonstrative, that connection is external to the probabilistic model that is used to determine the relevant conditional probability; hence, it does not complicate the update procedure.